Species diversity and distribution of Anuran at Similajau National Park, Bintulu, Sarawak, Malaysia - Saripuddin, Noor Bahiah (2018)
Tropical heath forest occurs widely in many places of Borneo. Similajau National Park is one of the locations with heath forest. Because of insufficient data on the anurans of heath forest in Similajau National Park, a survey was carried out beginning August 2014 until January 2015. The objectives of the study are compare the anuran species diversity between two different study plots and to determine anuran species microhabitat preferences. Sampling involved a 300m transects line and 240 quadrats method at both study sites. A total of 23 species of frogs (299 individuals) belonging to six frog families were detected. The study site was dominated by Dicroglossidae (48.8%) followed by Rhacophoridae (24.7%), Ranidae (17.7%), Ceratobatrachidae (4.7%), Microhylidae (1.3%) and Bufonidae (2.7%). In addition four endemic Borneo frogs namely Ingerophyrus divergens, Limnonectes ingeri, Kalophrynus intermedius, and Philautus tectus were also captured in this study. The Shannon Wiener Diversity Index, H’ at forest site was higher (2.48 ± 0.06) compared to non-forest site (1.77 ± 0.05).However, no dominant species at forest sites, which reflected the lowest Simpson Index, D was 0.091 (±0.01). In contrast, D at non forest sites was higher with 0.201 (±0.04) although the presence of Fejervarya cancrivora, with 59 individuals were recorded as dominance species for about 19.73% of the total frog sampled. The result of this study indicated that the species composition and diversity at Similajau National Park is still relatively higher than elsewhere. A study on habitat preference should be concluded that different species have their own associated microhabitats. It can also be concluded that the occurrences of individual’s species and richness depends on rainfall, relative humidity and temperature.